House rules : how to decorate for every home, style, and budget - Smith, Myquillyn (Revell, a division of Baker Publishing Group, 2024)
"New York Times bestselling author provides the simple rules to decorate by in this charming, definitive guidebook for hesitant decorators to move from "stuck" to "done.""--